2019
DOI: 10.1017/s1049023x19005193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Operator Position on the Quality of Chest Compressions Delivered in a Simulated Ambulance

Abstract: Background:Ambulances are where patient care is often initiated or maintained, but this setting poses safety risks for paramedics. Paramedics have found that in order to optimize patient care, they must compromise their own safety by standing unsecured in a moving ambulance.Hypothesis/Problem:This study sought to compare the quality of chest compressions in the two positions they can be delivered within an ambulance.Methods:A randomized, counterbalanced study was carried out with 24 paramedic students. Simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Third, previous studies have shown that the height at which the rescuer performs chest compressions signi cantly impacts CPR e ciency and rescuer fatigue. 9,25 In the present study, the axillary line height of the manikin uniformly placed on the dental chair was approximately 55 cm, which did not correspond to the appropriate position of each participant and may have affected e ciency and fatigue. Finally, this study did not use objective indices such as electrocardiogram, electromyography, or oxygen saturation to measure participants' physical fatigue, but only a subjective RPE scale fatigue assessment to ascertain subjects' sense of fatigue.…”
Section: Limitationsmentioning
confidence: 71%
“…Third, previous studies have shown that the height at which the rescuer performs chest compressions signi cantly impacts CPR e ciency and rescuer fatigue. 9,25 In the present study, the axillary line height of the manikin uniformly placed on the dental chair was approximately 55 cm, which did not correspond to the appropriate position of each participant and may have affected e ciency and fatigue. Finally, this study did not use objective indices such as electrocardiogram, electromyography, or oxygen saturation to measure participants' physical fatigue, but only a subjective RPE scale fatigue assessment to ascertain subjects' sense of fatigue.…”
Section: Limitationsmentioning
confidence: 71%
“…The participants also found chest compressions to be more effective when they were standing than when they were sitting. Thus, there is a strong correlation between the position of the rescuer in relation to the patient and the way the force is applied during CPR 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study was conducted in a simulated stationary ambulance in a laboratory setting, using a stretcher bed exclusively for the ambulance and a mannequin to test chest compressions by adjusting the bed height. The participants were not challenged by the acceleration, deceleration, and gravity inherent to moving ambulances 15 , 21 . Third, this study did not use objective electromyography (EMG) to measure the muscle fatigue of the participants; only the subjective RPE scale was used to understand the participants' perception of fatigue as an assessment of fatigue.…”
Section: Limitationsmentioning
confidence: 99%
“…Giving sitting position compression is safer for rescuers but reduces the quality of chest compressions given to the patient. Meanwhile, the standing position has a more optimal quality of chest compression to the patient but risks endangering the helper (Mullin et al, 2019).…”
Section: Amount Of Compressionmentioning
confidence: 99%